Safety and efficacy of co-administered diethylcarbamazine, albendazole and ivermectin during mass drug administration for lymphatic filariasis in Haiti: Results from a two-armed, open-label, cluster-randomized, community study. - Christine L Dubray; Anita D Sircar; Valery Madsen Beau de Rochars; Joshua Bogus; Abdel N Direny; Jean Romuald Ernest; Carl R Fayette; Charles W Goss; Marisa Hast; Kobie O'Brian; Guy Emmanuel Pavilus; Daniel Frantz Sabin; et al. (PLoS Neglected Tropical Diseases, 2020)
In Haiti, 22 communes still require mass drug administration (MDA) to eliminate lymphatic filariasis (LF) as a public health problem. Several clinical trials have shown that a single oral dose of ivermectin (IVM), diethylcarbamazine (DEC) and albendazole (ALB) (IDA) is more effective than DEC plus ALB (DA) for clearing Wuchereria bancrofti microfilariae (Mf). We performed a cluster-randomized community study to compare the safety and efficacy of IDA and DA in an LF-endemic area in northern Haiti. Ten localities were randomized to receive either DA or IDA. Participants were monitored for adverse events (AE), parasite antigenemia, and microfilaremia. Antigen-positive participants were retested one year after MDA to assess treatment efficacy. Fewer participants (11.0%, 321/2917) experienced at least one AE after IDA compared to DA (17.3%, 491/2844, P<0.001). Most AEs were mild, and the three most common AEs reported were headaches, dizziness and abdominal pain. Serious AEs developed in three participants who received DA. Baseline prevalence for filarial antigenemia was 8.0% (239/3004) in IDA localities and 11.5% (344/2994) in DA localities (<0.001). Of those with positive antigenemia, 17.6% (42/239) in IDA localities and 20.9% (72/344, P = 0.25) in DA localities were microfilaremic. One year after treatment, 84% percent of persons with positive filarial antigen tests at baseline could be retested. Clearance rates for filarial antigenemia were 20.5% (41/200) after IDA versus 25.4% (74/289) after DA (P = 0.3). However, 94.4% (34/36) of IDA recipients and 75.9% (44/58) of DA recipients with baseline microfilaremia were Mf negative at the time of retest (P = 0.02). Thus, MDA with IDA was at least as well tolerated and significantly more effective for clearing Mf compared to the standard DA regimen in this study. Effective MDA coverage with IDA could accelerate the elimination of LF as a public health problem in the 22 communes that still require MDA in Haiti.